“I Don’t Want to Be a Statistic”: Racial-Criminal Stigma, Redemption Bids, and Redemptive Generativity - Fader, Jamie J. (Crime & delinquency, 2024)
Within the context of racial caste and the “stickiness” of criminal labels, men struggle to craft positive masculine identities. Contesting racial-criminal stigma requires men of color to challenge controlling images of violent Black men. Analyzing narratives of 45 millennial men in Philadelphia, we identify redemption bids and redemptive generativity as ways of defying social stigma. Redemption, which has been highlighted in the desistance literature, is a central concern of the men of color we studied, regardless of prior law-breaking or system involvement. Because a criminal history is presumed regardless of past behavior, many men of color engage in performances of “making good” similar to those who were actively engaged in the work of desistance.